Camelina sativa L: an alternative in the semiarid region (Semiárida, 2023)
Camelina sativa L. (camelina) is an annual species primarily used as a second-generation biofuel. Compared to other winter crops, it helps with carbon sequestration, weed control, promotes nutrient recirculation, consumes low soil moisture from the profile, and allows early land use due to its short cycle. This communication presents the first study on the farming of camelina in Santa Rosa, La Pampa. To analyze the productive response of camelina, 25 experimental lines belonging to the company "Chacraservicios" were evaluated during the year 2022. The environmental conditions were suitable for camelina production, with an average yield of 729.4 kg.ha-1 and maximum yields of 1131 kg.ha-1, consistent with yields reported in other productive regions. Grain yield was largely explained by changes in biomass production (R2 = 0.80) and grains per square meter (R2 = 0.79). Lines 12, 21, and 18 showed promising results due to their high grain yield, biomass, and number of grains m2. The complexity of determining the adaptation of the species to the region, as well as identifying different genotypes, make it necessary to perform further evaluations to estimate yield, stability, and quality with more detail.
Keywords: camelina; yield; biomass; number of grain